Analisis Disiplin Kerja Dan Motivasi Terhadap Kinerja Karyawan Depot Air Nur Mutiara Tirta Di Bekasi - Dewi, Alya Mutiara; Azhar, Fatimah Nasywa; Syahla, Hanazka; Sulaeman, Eman (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This research aims to determine the influence of work discipline and motivation variables on employee performance at Depot Air Nur Mutiara Tirta. The data collection methods used were interviews with one of the employees and the business owner, as well as direct observation of the company. The results of the study indicate a direct and significant positive relationship between work discipline and motivation variables and the variable of employee performance. Work discipline has a greater impact on employee performance compared to motivation. The implication of this research is that the company needs to pay attention to the work discipline of employees, especially in terms of compliance with the rules and procedures set by the business owner. Additionally, motivation also needs to be improved to enhance employee performance. In conclusion, both work discipline and motivation variables have a significant influence on employee performance in the company, and these factors need to be considered by the company to enhance employee performance.